MEDICINAL PLANTS: TYPES, BENEFITS, AND METHODS OF USE (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2024)
This article analyzes the types of medicinal plants, their benefits, and methods of use from a scientific perspective. Medicinal plants have positive effects on various systems of the body and have been used in traditional medicine for centuries. The article presents the most popular medicinal plants (Aloe vera, Chamomile, Lavender, Echinacea, Ginseng, Turmeric, Ginkgo biloba) and their main benefits. Additionally, the article examines various methods of using these plants and the scientific basis for improving health through their use.